Pemeriksaan HIV pada Darah Pendonor di Unit Tranfusi Darah RSUD Kabanjahe - WARDHANI, SRI MURI DASA; POHAN, IKHSAN IBRAHIM; SIREGAR, SRI HANDAYANI (Journal of Engineering and Information Technology for Community Service, 2024)
HIV (Human Immunodeficiency Virus) is a virus that can cause AIDS by attacking white blood cells called CD4 cells and can damage the human immune system so that the body is no longer able to fight incoming diseases. The medium of transmission of HIV/AIDS can be the bloodstream in the form of wounds, sperm fluid and vaginal fluid. The way of transmission can be through sexual intercourse, blood transfusion, needle use and through HIV-infected pregnant women to their children. HIV testing of blood donors in the Blood Transfusion Unit of Kabanjahe Regional Hospital from January to February 2019 was conducted with the aim of determining the presence or absence of the HIV virus in the blood of donors. This examination is descriptive using the Rapid Test method, with a sample of 41 people and obtained results as many as 37 people (96.24%) donor blood is not infected with HIV and 4 people (9.76%) donor blood is infected with HIV. It is expected to the reader to be more careful in receiving donor blood or using needles, and to the relevant agencies to further improve the supervision and examination of donor blood.